Nutritional management of athletes with Type 1 diabetes: a narrative review - Cavallo, M.; De Fano, M.; Barana, L.; Dozzani, I.; Bianchini, E.; Pellegrino, M.; Cisternino, L.; Migliarelli, S.; Giulietti, C.; Pippi, R.; Fanelli, C. G. (Nutrients, 2024)
Type 1 diabetes mellitus (T1DM) represents a complex clinical challenge for health systems. The autoimmune destruction of pancreatic beta cells leads to a complete lack of insulin production, exposing people to a lifelong risk of acute (DKA, coma) and chronic complications (macro and microvascular). Physical activity (PA) has widely demonstrated its efficacy in helping diabetes treatment. Nutritional management of people living with T1DM is particularly difficult. Balancing macronutrients, their effects on glycemic control, and insulin treatment represents a complex clinical challenge for the diabetologist. The effects of PA on glycemic control are largely unpredictable depending on many individual factors, such as intensity, nutrient co-ingestion, and many others. Due to this clinical complexity, we have reviewed the actual scientific literature in depth to help diabetologists, sport medicine doctors, nutritionists, and all the health figures involved in diabetes care to ameliorate both glycemic control and the nutritional status of T1DM people engaging in PA. Two electronic databases (PubMed and Scopus) were searched from their inception to January 2024. The main recommendations for carbohydrate and protein ingestion before, during, and immediately after PA are explained. Glycemic management during such activity is widely reviewed. Micronutrient needs and nutritional supplement effects are also highlighted in this paper.